Esophagogastrostomi dengan Stapler Linear Murny Rauf pada Achalasia Tipe III – Laporan Kasus: Laporan Kasus - Djunaedi, Angela; Nitbani, Alders Alen Kusa; Marino, Widhitomo (Cermin Dunia Kedokteran, 2026)
Introduction: Feeding difficulty is one of the main complaints of patients with achalasia. Achalasia is still considered a rare disorder with unknown etiology. The main goal of the treatment is to increase the patient’s quality of life and treat dysphagia to improve food intake.A successful esophagogastrostomy Murny Rauf procedure for achalasia treatment in a limited-resource hospital is presented. Case: A 47-year-old woman was diagnosed with type III achalasia (Eckardt’s score: 12) and severe malnutrition. The esophagogastrostomy with the Murny Rauf procedure was conducted to increase food intake. The patient gained weight due to improved feeding several weeks after the surgery. Discussion: Diagnosis of achalasia is made by clinical symptoms and confirmed by a diagnostic procedure. In this case, nonsurgical medications were not considered due to the uncertainty of the benefit and difficulties of routine visits due to the far distance of the patient’s residence to the hospital which may incur additional transportation costs. Conclusion: The esophagogastrostomy Murny Rauf procedure provides advantages in treating achalasia. This procedure gave a new insight into developing an efficient procedure for achalasia in rural areas.